Ribosomal DNA transcription in prefrontal pyramidal neurons is decreased in suicide - Krzyżanowska, Marta; Steiner, Johann; Pieśniak, Dorota; Karnecki, Karol; Kaliszan, Michał; Wiergowski, Marek; Rębała, Krzysztof; Brisch, Ralf; Braun, Katharina; Jankowski, Zbigniew; Kosmowska, Monika; Chociej, Joanna; et al. (European archives of psychiatry and clinical neuroscience, 2020)
Prefrontal cortical regions, which are crucial for the regulation of emotionally influenced behaviour, play most probably a dominant role in the pathogenesis of suicide. The study was carried out on paraffin-embedded brain tissue blocks containing specimens from the anterior cingulate cortex (dorsal and ventral parts), the orbitofrontal cortex, and the dorsolateral cortex obtained from 23 suicide completers (predominantly violent) with unknown psychiatric diagnosis and 25 non-suicidal controls. The transcriptional activity of ribosomal DNA (rDNA) as a surrogate marker of protein biosynthesis was evaluated separately in layers III and V pyramidal neurons in regions of interest (ROIs) mentioned above by the AgNOR silver staining method bilaterally. The overall statistical analysis revealed a decrease of AgNOR area suggestive of attenuated rDNA activity in suicide victims versus controls, particularly in male subjects. Further ROI-specific post-hoc analyses revealed decreases of the median AgNOR area in suicides compared to non-suicides in all 16 ROIs. However, this effect was only significant in the layer V pyramidal neurons of the right ventral anterior cingulate cortex. Our findings suggest that decreased rDNA transcription in prefrontal pyramidal neurons plays possibly an important role in suicide pathogenesis.